THE EFFECT OF SUSTAINABILITY REPORTING ON COMPANY PERFORMANCE - Felita, Arina; Faisal, Faisal (Diponegoro Journal of Accounting, 2021)
The aim of this study is to examine the influence of sustainability reporting on company performance. The variable control of this study used total asset, return on asset, return on equity and net interest margin. This populations consists of financial company especially the banking sector in Indonesia Stock Exchange for the period 2016-2019. Sampling method determined by purposive sampling. The final sample of this research is 85 companies. This study used multiple regression analysis for hypotheses testing. The results of this study show that sustainability reporting positively influence the company performance.